2000
DOI: 10.1177/004051750007001106
|View full text |Cite
|
Sign up to set email alerts
|

Treating Denim Fabrics with Trichoderma Reesei Cellulases

Abstract: Cellulases are widely used to age denim fabrics. In this work the effects of three purified monocomponent cellulases, EG I, EG II, and CBH I, and two different cellulase mixtures produced by genetically modified strains of Trichoderma reesei are compared for stone washing denim fabrics. Stone washing effects are evaluated by analyzing the soluble reducing sugars, absorbance, and lightness values of the treatment solutions. The prop erties of denim swatches are evaluated by reflectance units and by a panel. Pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 9 publications
1
44
0
1
Order By: Relevance
“…Biostoning of fabric means the use of cellulases in place of, or in addition to, the use of pumice stones for the treatment of denim fabric to impart a stonewashed effect. Heikinheimo et al (7) showed that T. reesei-purified cellulase EGII was the most effective at removing color from denim, producing a good stonewashing effect with the lowest hydrolysis level. Endoglucanases are important also for degradation of ␤-glucan in feed.…”
mentioning
confidence: 99%
“…Biostoning of fabric means the use of cellulases in place of, or in addition to, the use of pumice stones for the treatment of denim fabric to impart a stonewashed effect. Heikinheimo et al (7) showed that T. reesei-purified cellulase EGII was the most effective at removing color from denim, producing a good stonewashing effect with the lowest hydrolysis level. Endoglucanases are important also for degradation of ␤-glucan in feed.…”
mentioning
confidence: 99%
“…Oxidative bleaching agent with or without the addition of stones have also been used to get fading effect. Difficulty in removing residual pumice from fabric, damage to equipment and clogging of machine drainage passage due to particulate material proved to be major drawbacks with the technique (Heikinheimo et al 2000). Later on use of enzymes became a sustainable option to get the worn out look in denim.…”
Section: Introductionmentioning
confidence: 99%
“…Denim fabric has been treated with Trichoderma Reesei cellulases and compared for stone washing denim fabrics (Heikinheimo et al 2000). The redeposition of indigo after treating with cellulase has been examined to certain extent .…”
Section: Introductionmentioning
confidence: 99%
“…The optimal pH for a particular cellulase depends upon its origin (Schindler and Hauser 2004). Commercial cellulases for biopolishing originate from Trichoderma reesei and Humicola insolens (Azevedo et al 2000;Heikinheimo et al 2000). Acid cellulases are Trichodermabased products which work best at pH 4.5-5.5 at a temperature of 45-55°C (Shah 2014;Choudhury 2006).…”
Section: Introductionmentioning
confidence: 99%